Pengaruh pembelajaran matematika realistik ditinjau dari gaya belajar mahasiswa Teknik Sipil - Hr, Bq. Malikah; Sukandi, Sukandi; Dewi, Ni Putu Ety Lismaya (Media Pendidikan Matematika, 2021)
The research aims to know the effect of realistic mathematics learning in mathematics-II courses seen from the learning styles of Civil Engineering students. This type of research uses a quasi-experimental with a 2 x 3 factorial design. The sample consists of 30 second-semester students of Civil Engineering of Mandalika university of Education. The instruments in the research were a learning style questionnaire and an essay test that contained questions for mathematics II courses. The test of data analysis using two-way analysis of variance. The results showed that the learning method and learning style had a significant effect on student learning outcomes in mathematics II courses. The influence of learning methods was 26.8% and the influence of student learning styles was 37.8%. Based on the marginal average, the average of students with realistic mathematics learning methods was 70.73 and the average of students with conventional methods was 65.93. In a class that was treated with realistic mathematics learning, the average of students with visual learning styles was 75.80, the average of students with auditory learning styles was 70.80 and the average of students with kinesthetic learning styles was 65.60. It was concluded that in mathematics II courses, the application of realistic mathematics learning was effective in improving student learning outcomes and students with visual learning styles had better learning outcomes than students with auditory and kinesthetic learning styles and students auditory learning styles had better learning outcomes than students with kinesthetic learning styles.